Regulation of Pancreatic Juxtaductal Endocrine Cell Formation by FoxO1 - Kitamura, Tadahiro (American Society for Microbiology (ASM), 2009)
An understanding of the mechanisms that govern pancreatic endocrine cell ontogeny may offer strategies for their somatic replacement in diabetic patients. During embryogenesis, transcription factor FoxO1 is expressed in pancreatic progenitor cells. Subsequently, it becomes restricted to β cells and to a rare population of insulin-negative juxtaductal cells (FoxO1(+) Ins(−)). It is unclear whether FoxO1(+) Ins(−) cells give rise to endocrine cells. To address this question, we first evaluated FoxO1's role in pancreas development using gain- and loss-of-function alleles in mice. Premature FoxO1 activation in pancreatic progenitors promoted α-cell formation but curtailed exocrine development. Conversely, FoxO1 ablation in pancreatic progenitor cells, but not in committed endocrine progenitors or terminally differentiated β cells, selectively increased juxtaductal β cells. As these data indicate an involvement of FoxO1 in pancreatic lineage determination, FoxO1(+) Ins(−) cells were clonally isolated and assayed for their capacity to undergo endocrine differentiation. Upon FoxO1 activation, FoxO1(+) Ins(−) cultures converted into glucagon-producing cells. We conclude that FoxO1(+) Ins(−) juxtaductal cells represent a hitherto-unrecognized pancreatic cell population with in vitro capability of endocrine differentiation.